2012
DOI: 10.1002/mnfr.201200383
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D reduces the inflammatory response and restores glucose uptake in adipocytes

Abstract: The improvement of both proinflammatory status and glucose uptake in adipocytes under 1,25-(OH)(2) D(3) effect suggests that low-grade inflammation could be linked to vitamin D deficiency. This observation offers new perspectives in the context of obesity and associated physiopathological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
110
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 45 publications
(61 reference statements)
16
110
0
2
Order By: Relevance
“…These results have since been challenged by several groups (67,(75)(76)(77) who consistently report anti-inflammatory effects of 1,25 (OH) 2 D whatever the model studied, which fits better with the well-described anti-inflammatory effect of VD in many other cell types (78) . Indeed, it was shown that 1,25(OH) 2 D significantly decreased the release of IL-8, monocyte chemoattractant protein (MCP)-1 and IL-6 by human preadipocytes (76) and MCP-1 by human adipocytes (75) .…”
Section: Regulation Of Inflammationmentioning
confidence: 76%
See 1 more Smart Citation
“…These results have since been challenged by several groups (67,(75)(76)(77) who consistently report anti-inflammatory effects of 1,25 (OH) 2 D whatever the model studied, which fits better with the well-described anti-inflammatory effect of VD in many other cell types (78) . Indeed, it was shown that 1,25(OH) 2 D significantly decreased the release of IL-8, monocyte chemoattractant protein (MCP)-1 and IL-6 by human preadipocytes (76) and MCP-1 by human adipocytes (75) .…”
Section: Regulation Of Inflammationmentioning
confidence: 76%
“…Similarly, 1,25(OH) 2 D reduced the expression of IL-6, IL-8 and MCP-1 in human adipose tissue biopsies submitted to IL-1β stimulation in vitro (79) . The molecular mechanisms have been investigated, and VDR and NF-κB signalling pathways and p38 mitogen-activated protein kinases were shown to be involved in 3T3-L1 adipocytes (67) . Interestingly, Zoico et al recently demonstrated that VD, similarly to 1,25(OH) 2 D, was able to blunt the lipopolysaccharide-mediated pro-inflammatory effect in human adipocytes (37) .…”
Section: Regulation Of Inflammationmentioning
confidence: 99%
“…Vitamin D receptors (VDR) present in adipocytes allow the suppression of Parathyroid hormone (PTH) levels. The PTH excess observed in menopausal women with both primary and secondary hyperparathyroidism may promote weight gain by impeding catecholamine-induced lipolysis [50]. A previous study showed that Vit D has a positive effect on muscle mass, especially on fat free mass, and also on muscle activity [4].…”
Section: Discussionmentioning
confidence: 99%
“…VDR variant BsmI may impact the binding of 1,25(OH) 2 D 3 to VDR and further could mediate a mass of downstream effects on VDR-responsive genes. The effect of VDR Bsm1 variant polymorphism could be direct mediating effects through the immune system and inflammatory pathway by alteration of the inflammation is possibly resulting from the gut microbial translocation [13,27]. In addition, The BsmI, and TaqI polymorphism are located in the 3' untranslated region (3′ UTR) of the VDR gene.…”
Section: Discussionmentioning
confidence: 99%
“…All anthropometric measurements were evaluated in the Nutrition DepartmentQatar University by trained instructors. BMI categorized into the following categories: underweight (<18.5), normal weight (18.5-24.9), overweight (25)(26)(27)(28)(29)(30), and obese (>30) [19], % body fat for females >30% is used as a cut-off point to define obesity [20] and if waist circumference (WC) >88cm is used to define central obesity [21]. The homeostatic model assessment (HOMA) is used to quantify insulin resistance and beta-cell function, whereas HOMA-IR=[Glucose in mmol/l] * [Insulin in mU/L]/22.5 [22].…”
Section: Adiposity Phenotype Measurementsmentioning
confidence: 99%